Th17 Cell-Mediated Neuroinflammation Is Involved in Neurodegeneration of Aβ1-42-Induced Alzheimer’s Disease Model Rats - Jun Zhang; Kaifu Ke; Zhan Liu; Yihua Qiu; Yu-Ping Peng (2013)
Neuroinflammation, especially innate immunocyte-mediated neuroinflammation, has been reported to participate in pathogenesis of Alzheimer's disease (AD). However, the involvement of adaptive immune cells, such as CD4(+) T lymphocytes, in pathogenesis of AD is not well clarified. Herein, we focus on T helper 17 (Th17) cells, a subpopulation of CD4(+) T cells with high proinflammation, and show the implication of the cells in neurodegeneration of AD. Amyloid β1-42 (Aβ1-42) was bilaterally injected into hippocampus of rats to induce AD. On days 7 and 14 following the Aβ1-42 administration, escape latency of the rats in Morris water maze was increased, expression of amyloid precursor protein was upregulated, but expression of protein phosphatase 2A was downregulated in the hippocampus, and Nissl stain showed neuronal loss and gliosis in CA1 region. Infusion of FITC-linked albumin in blood circulation and combination with immunostaining of hippocampal sections for RORγ, a specific transcriptional factor of Th17 cells, demonstrated blood-brain barrier (BBB) disruption and Th17 cells' infiltration into brain parenchyma of AD rats. Expression of Th17 proinflammatory cytokines, interleukin (IL)-17 and IL-22, was increased in the hippocampus, and concentrations of the two cytokines were elevated in both the cerebrospinal fluid and the serum in AD occurrence and development. Compared with intact or saline-treated control rats, AD animals indicated an upregulated expression of Fas and FasL in the hippocampus. Further, the immunofluorescent histochemistry on AD hippocampal sections with NeuN, RORγ, Fas and FasL displayed that Fas was principally expressed by neurons and FasL was predominantly expressed by Th17 cells, and that neuronal apoptosis shown by TUNEL and NeuN double-labeled cells increased. These results suggest that Th17 cells, which were infiltrated into AD brain parenchyma, participate in neuroinflammation and neurodegeneration of AD by release of proinflammatory cytokines and by direct action on neurons via Fas/FasL apoptotic pathway.